The Epistemology of Collective Testimony - Townsend Leo (Journal of Social Ontology, 2021)
In this paper, I explore what gives collective testimony its epistemic credentials, through a critical discussion of three competing accounts of the epistemology of collective testimony. According to the first view, collective testimony inherits its epistemic credentials from the beliefs the testimony expresses—where this can be seen either as the beliefs of all or some of the group’s members, or as the beliefs of group itself. The second view denies any necessary connection to belief, claiming instead that the epistemic credentials of collective testimony derive from the reliability or truth-conduciveness of the statement that expresses the testimony. Finally, the third view claims that the epistemic credentials of collective testimony derive from the fact that it involves undertaking a collective commitment to trustworthiness, which makes the group susceptible to rebuke and blame if its testimony is not trustworthy. I argue that this last account holds the most promise for preserving what is distinctive about testimonial knowledge while still underwriting a robust epistemology of collective testimony.